DEVELOPMENT OF PLURALISTIC RURAL GOVERNMENT WITHIN THE PANCASILA IDEOLOGY IN INDONESIA - Sufian Hamim; Syafhendry; Rahyunir Rauf; Syarifah Ermayuna; Fabellany Sovina (Proceeding International Conference on Social Sciences, 2026)
The importance of rural development with a pluralistic socio-cultural approach in the Indonesian rural government system. Formulation, As a research objective how development and public services can be implemented effectively in a highly pluralistic society, consisting of various ethnic groups, and adhering to various religions and beliefs in the Pancasila Ideology system and the 1945 Constitution. The research procedure uses survey and collaborative participatory methods with target groups. With qualitative analysis. The research location is in 2 Villages 2 Indragiri Hilir Regency and Kampar Regency as a Sample of Riau Province. The results of the study show that Tribe, Religion, Race, and Inter-Group (SARA) are an inseparable part that is always present and well maintained in the social and cultural life of rural communities in Indonesia. The existence and dynamics of rural communities are maintained, growing mutual understanding, tolerance, prosperity and fair treatment. The formal structure of village government becomes an "official framework" where the representation of the interests of citizens of various ethnicities, religions, and social classes can be accommodated through role placement mechanisms, deliberation procedures, and accountable decision-making. While there is no uniformity in naming villages, there is a uniform organizational structure for village government in Indonesia, while still recognizing differences and the rights of local socio-cultural origins. The concept of differences between ethnicities, religions, races, and groups, which are pluralistic, does not contribute to conflicts in filling government positions in Indonesian villages. Political pluralism believes that power should not be concentrated in one group. Public decisions should ideally be the result of competition and negotiation between different interest groups, while maintaining equal access. Formal and informal figures have been found to be unifying factors in government pluralism in village development in Indonesia. The independence of public services in pluralistic rural communities in Indonesia is a concept that emphasizes the importance of public services that are free from political, religious, or group influence. A consistent strategy is needed to implement the principles of pluralistic governance in development and public services in rural Indonesia, namely: transparency, accountability, responsiveness, independence, fairness, and justice.